Analisis Kepuasan Alumni Terhadap Pelayanan Akademik dengan Metode Importance Performance Analysis Berbasis Web (Studi Kasus: Universitas CIC) - Marsani Asfi; Kusnadi Kusnadi; Kristianto Kristianto (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Increasing development of information technology and competition among tertiary institutions, analysis quality of academic services in the competitive era such as now is an important thing for university to do. The purpose of this research is to build a web-based computer system for analyzing alumni satisfaction with the quality of academic services at CIC University, the sample data used were 31 Alumni CIC University who graduates in 2019. The analytical method used was Importance Performance Analysis method, this method is an analysis technique which is used to find out which attributes have a big influence on satisfaction, where the measured attributes will be grouped in 4 quadrants. The results of this research is alumni satisfaction analysis systems for academic services at CIC University with Importance Performance Analysis method. The results of the system test of 31 alumni sample data assessing 9 attributes of academic services at CIC University, obtained 33.33% or 3 attributes included in Quadrant I which means that attributes are recommended to be improved. 11.11% or 1 attribute included in the Quadrant II, it mean that attribute has succeeded in satisfying the Alumni and its performance must be maintained. 22.22% or 2 attributes are in the Quadrant III category, it mean that atrributes have a low priority to be improved. While in Quadrant IV there are 33.33% or 3 attributes, it mean that these attributes have good performance, but are not considered important by Alumni